Occupational back pain among nurses: A challenge to the quality of care in the city of Kindu, Democratic Republic of the Congo - Ngereza, A. M.; Masudi, J. P. M.; Mabakutuvangilanga, Simon-Decap (Orapuh Journal, 2025)
Introduction Lower back pain among nurses represents a common yet insufficiently investigated occupational health issue. Purpose This study aimed to determine the prevalence and contributory factors associated with lower back pain among nursing professionals in Kindu. Methods A total of 165 nurses from two institutions—Kindu General Referral Hospital and Lumbulumbu Mapon Hospital Centre—were included. Data were collected using a structured questionnaire. Chi-square tests were applied to determine correlations between potential risk factors and the occurrence of lower back pain. Results The prevalence of lower back pain was 70%. Significant associated factors included professional seniority of less than five years (OR = 1.5; 95% CI: 1.1–2.0; p = 0.03), educational level (OR = 1.4; 95% CI: 1.0–1.9; p = 0.04), prolonged standing (OR = 1.3; 95% CI: 0.9–1.7; p = 0.03), lack of training in patient lifting techniques (OR = 1.4; 95% CI: 1.0–1.7; p = 0.03), and absence of assistive equipment (OR = 1.3; 95% CI: 1.0–1.7; p = 0.04). Emotional stress (OR = 1.3; 95% CI: 1.0–1.7; p = 0.04), time pressure (OR = 1.3; 95% CI: 1.0–1.7; p = 0.01), and lack of psychological support (OR = 1.3; 95% CI: —; p ≤ 0.04) were also significantly correlated with the incidence of lower back pain. Conclusion Effective management of occupational lower back pain among nurses calls for targeted ergonomic training, provision of lifting aids, and comprehensive strategies to improve working conditions and the overall quality of patient care.